The Effect of Customer Relationship Management, Digital Advertising, and Discount Programs on Customer Loyalty at Start-ups in Jakarta - Sudirjo, Frans; Faridah, Faridah; Astutik, Wahyuni Sri; Vandika, Arnes Yuli (West Science Interdisciplinary Studies, 2024)
This study investigates the influence of Customer Relationship Management (CRM), digital advertising, and discount programs on customer loyalty at a start-up company in Jakarta. Utilizing a quantitative research methodology, data were collected from 180 respondents through a structured questionnaire employing a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that all hypotheses are positive and significant, demonstrating that effective CRM practices, strategic digital advertising, and attractive discount programs significantly enhance customer loyalty. Specifically, CRM showed a path coefficient of 0.293, digital advertising 0.223, and discount programs 0.351, with all paths being statistically significant. These results underline the critical role of integrated marketing strategies in fostering strong customer relationships and loyalty in the competitive start-up environment.